1983
DOI: 10.1017/s0022029900032684
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of Debaryomyces hansenii towards Clostridium tyrobutyricum and Cl. butyricum

Abstract: SUMMARYA study of the inhibitory action of Debaryomyces hansenii (31 strains) on Clostridium tyrobutyricum (5 strains) and Cl. butyricum (2 strains) on laboratory media showed that Deb. hansenii inhibited the growth of these organisms, and that this effect was due not only to competition for nutrients but also to the production of both extra-and intracellular antimicrobial metabolites. The inhibitory effect varied with strain and occurred whether the yeasts were grown aerobically or under reduced O2 tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 7 publications
(1 reference statement)
0
26
0
1
Order By: Relevance
“…In semisoft cheeses with surface films and in mold-ripened cheeses, D. hansenii utilizes lactic acid as a main carbon source and produces ammonia by proteolysis, leading to an increase of pH that stimulates growth of other microorganisms during the second stage of maturation (2,4). The predominance of D. hansenii in a number of fermented dairy products prevents spoilage by clostridial species through the production of antibacterial metabolites (14). In addition, D. hansenii produces a killer toxin that is active against various yeast species and molds (19,27).…”
Section: Discussionmentioning
confidence: 99%
“…In semisoft cheeses with surface films and in mold-ripened cheeses, D. hansenii utilizes lactic acid as a main carbon source and produces ammonia by proteolysis, leading to an increase of pH that stimulates growth of other microorganisms during the second stage of maturation (2,4). The predominance of D. hansenii in a number of fermented dairy products prevents spoilage by clostridial species through the production of antibacterial metabolites (14). In addition, D. hansenii produces a killer toxin that is active against various yeast species and molds (19,27).…”
Section: Discussionmentioning
confidence: 99%
“…This yeast is also an important co-starter for the cheesemaking industry [19] due to its proteolytic and lipolytic activity, its compatibility and stimulating action with lactic acid starter cultures, inhibition of growth of spoilage bacteria [9,16,18,34,38,45] and tolerance to changes in salt conditions. D. hansenii is one of the most common yeast species found in different types of cheese.…”
Section: Introductionmentioning
confidence: 99%
“…This species also provides proteolytic and lipolytic activities during cheese ripening. It was also reported that D. hansenii inhibits the growth of spoilage bacteria of the genus Clostridium [5]. The distribution of yeasts of this species at the surface and within the cheese depends on the type of cheese considered [2,3].…”
Section: Introductionmentioning
confidence: 99%